Where the spirit lives - St. John, Michelle 1967-; MacDonald, Ann-Marie 1958-; Hemblen, David 1941-2020; Leckie, Keith Ross 1952-; Pittman, Bruce 1950- (Studio Entertainment, 1989)
Indian children in western Canada are taken from their homes by trickery, put in mission schools, and brutally forced to learn non-Indian ways